Identification of Novel Genes and Biological Pathways That Overlap in Infectious and Nonallergic Diseases of the Upper and Lower Airways Using Network Analyses - Baschal, Erin E.; Larson, Eric D.; Bootpetch Roberts, Tori C.; Pathak, Shivani; Frank, Gretchen; Handley, Elyse; Dinwiddie, Jordyn; Moloney, Molly; Yoon, Patricia J.; Gubbels, Samuel P.; Scholes, Melissa A.; Cass, Stephen P.; et al. (Frontiers in Genetics, 2020)
Previous genetic studies on susceptibility to otitis media and airway infections have focused on immune pathways acting within the local mucosal epithelium, and outside of allergic rhinitis and asthma, limited studies exist on the overlaps at the gene, pathway or network level between the upper and lower airways. In this report, we compared [1] pathways identified from network analysis using genes derived from published genome-wide family-based and association studies for otitis media, sinusitis and lung phenotypes, to [2] pathways identified using differentially expressed genes from RNA-sequence data from lower airway, sinus and middle ear tissues, in particular cholesteatoma tissue compared to middle ear mucosa. For otitis media, a large number of genes (n=1,806) were identified as differentially expressed between cholesteatoma and middle ear mucosa, which in turn led to the identification of 68 pathways that are enriched in cholesteatoma. Two differentially expressed genes CR1 and SAA1 overlap in middle ear, sinus and lower airway samples and are potentially novel genes for otitis media susceptibility. In addition, 56 genes were differentially expressed in both tissues from the middle ear and either sinus or lower airways. Pathways that are common in upper and lower airway diseases, whether from published DNA studies or from our RNA-sequencing analyses, include chromatin organization/remodeling, endocytosis, immune system process, protein folding, and viral process. Taken together, our findings from genetic susceptibility and differential tissue expression studies support the hypothesis that the unified airway theory wherein the upper and lower respiratory tracts act as an integrated unit also applies to infectious and non-allergic airway epithelial disease. Our results may be used as reference for identification of genes or pathways that are relevant to upper and lower airways, whether common across sites, or unique to each disease.